The early innate response of chickens to Salmonella enterica is dependent on the presence of O-antigen but not on serovar classification. - Karolina Varmuzova; Marta Elsheimer Matulova; Alena Sebkova; Zuzana Sekelova; Hana Havlickova; Frantisek Sisak; Vladimir Babak; Ivan Rychlik (PLoS ONE)
Salmonella vaccines used in poultry in the EU are based on attenuated strains of either Salmonella serovar Enteritidis or Typhimurium which results in a decrease in S. Enteritidis and S. Typhimurium but may allow other Salmonella serovars to fill an empty ecological niche. In this study we were therefore interested in the early interactions of chicken immune system with S. Infantis compared to S. Enteritidis and S. Typhimurium, and a role of O-antigen in these interactions. To reach this aim, we orally infected newly hatched chickens with 7 wild type strains of Salmonella serovars Enteritidis, Typhimurium and Infantis as well as with their rfaL mutants and characterized the early Salmonella-chicken interactions. Inflammation was characterized in the cecum 4 days post-infection by measuring expression of 43 different genes. All wild type strains stimulated a greater inflammatory response than any of the rfaL mutants. However, there were large differences in chicken responses to different wild type strains not reflecting their serovar classification. The initial interaction between newly-hatched chickens and Salmonella was found to be dependent on the presence of O-antigen but not on its structure, i.e. not on serovar classification. In addition, we observed that the expression of calbindin or aquaporin 8 in the cecum did not change if inflammatory gene expression remained within a 10 fold fluctuation, indicating the buffering capacity of the cecum, preserving normal gut functions even in the presence of minor inflammatory stimuli.